(untitled) (Fiep Bulletin - online, 2016)
, with 73 females and 97 males with a mean age of 37.77 years were evaluated. The main goal of fitness enthusiasts is health (42%). Regarding practice time, perform zero to six months (42%) with a frequency of 3.79 days per week and duration of 84.85 minutes. Activities are held 45% friend (them), and 39% chose the Orla space / environment. Individuals are mostly browns (51%), unmarried (61%), university graduates (46%), meet workday between 20-40 hours per week (57%) and the Economic Class B belong (52%). From, the profile of these individuals, it is possible to suggest management strategies and planning policies for sport and leisure, through more effective for health promotion and prevention of physical activities.